Surgical treatment of patients with myopathic ptosis - M. A. Zakharova; M. G. Kataev (Российский офтальмологический журнал)
Myopathic ptosis can occur in mitochondrial myopathies, oculopharyngeal muscular dystrophy or myotonic dystrophy and have common clinical characteristics. The management of myopathic ptosis is challenging due to a high risk of postoperative lagophthalmos. In this study, we report the results of surgical treatment in patients with myopathic ptosis. Purpose: to evaluate the results of treatment of patients with myopathic ptosis of the upper eyelids, operated in various ways, and propose an algorithm for choosing the method of treatment. Materials and methods. A retrospective study of 11 patients (10 females and 1 male) with myopathic ptosis was conducted. Surgical treatment included frontalis suspension using mersilene mesh with levator function ≤ 4 mm, (6 patients), resection of the levator and muscle of Muller with levator function ≥5 mm (5 patients). If excess skin of the upper eyelids was available, resection of the skin and orbicularis was additionally performed in both surgery techniques. Results. In all cases, positive values of the postoperative Marginal Reflex Distance (MRD1 = 0.5-2 mm) were obtained. Postoperative lagophthalmos was observed in two patients who underwent a recession of suspensions in an early postoperative period. In one case, the mersilene mesh was exposed on both eyes 12 months after surgery. Conclusion. The positive effect of the surgical treatment of myopathic ptosis is determined by eyelid opening to reach the values of MRD1 of at least 0 mm and a complete absence of lagophthalmos. The choice of the method of treatment is based on the correlation of levator function and the mobility of the eyebrows. In excess skin, both surgical methods are supplemented with skin and orbicularis resection. The appearance of any lagophthalmos in the postoperative period is an indication for an early corrective operation. For citation: Zakharova M.A., Kataev M.G. Surgical treatment of patients with myopathic ptosis. Russian ophthalmological journal. 2018; 11 (1): 74-9. doi: 10.21516/2072-0076-2018-11-1-74-79 (In Russian).